2009
DOI: 10.1007/s10827-009-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of gain modulation in brainstem circuits: VOR control system

Abstract: Gain modulation is believed to be a common integration mechanism employed by neurons to combine information from various sources. Although gain fields have been shown to exist in some cortical and subcortical areas of the brain, their existence has not been explored in the brainstem. In the present modeling study, we develop a physiologically relevant simplified model for the angular vestibulo-ocular reflex (VOR) to show that gain modulation could also be the underlying mechanism that modifies VOR function wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…The model structure and connections are similar to the one developed in [9] with linear summing junctions except for nonlinear canals and nonlinear EHV cells. It should be noted that some known connections, i.e.…”
Section: B Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model structure and connections are similar to the one developed in [9] with linear summing junctions except for nonlinear canals and nonlinear EHV cells. It should be noted that some known connections, i.e.…”
Section: B Model Descriptionmentioning
confidence: 99%
“…EHV cells are known to behave nonlinearly and also exhibit vergence dependent behavior [21], [5], [22]. In the former model [9], context dependency relied on a single nonlinearity applied after the sum of EHV afferent signals. Therefore, as different gains were generated with viewing context, the dynamics of the system also changed.…”
Section: B Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous nonlinear identification algorithms, as well as modeling studies by Galiana et al [7][8][9][10] have also proposed that healthy human subjects could exhibit nonlinear integration characteristics during VOR movements. They also suggested that perhaps the neural integrator time constant is highest closer to the origin and declines at lateral positions.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic search coil measurements in goldfish during spontaneous scanning of the surroundings also revealed nonlinear P-V plots, suggesting that at least in goldfish integrator function depends on eye position in the orbit [5]. There are also several modeling studies [6][7][8][9][10][11] NI network, although these predictions have not yet been verified by experimental studies. In this article we present the results of gaze-holding experiments in healthy human subjects, using videooculography technique.…”
Section: Introductionmentioning
confidence: 99%